The Japanese Power Elite - Rothacher, Albrecht. author. aut Link
XIX, 311 p.
Keywords: This book attempts a coherent portrait of the heart of Japan's economic and political decision making. It presents the men occupying the core positions in Japan's ruling party, the central ministries, and in big business and its organizations. Elite career patterns, social origins, upbringing, university education, cognitive orientations and ways of life are reviewed, as are the interactions in the exclusive world of Japan's increasingly hereditary and bureaucratic class of power holders in conservative politics and big business.